2012
DOI: 10.1100/2012/416321
|View full text |Cite
|
Sign up to set email alerts
|

Distributions, Sources, and Backward Trajectories of Atmospheric Polycyclic Aromatic Hydrocarbons at Lake Small Baiyangdian, Northern China

Abstract: Air samples were collected seasonally at Lake Small Baiyangdian, a shallow lake in northern China, between October 2007 and September 2008. Gas phase, particulate phase and dust fall concentrations of polycyclic aromatic hydrocarbons (PAHs) were measured using a gas chromatograph-mass spectrometer (GC-MS). The distribution and partitioning of atmospheric PAHs were studied, and the major sources were identified; the backward trajectories of air masses starting from the center of Lake Small Baiyangdian were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…When performing PCA with the sample size smaller than the number of variables, (n < 17 in the case of PCDD/F), the KMO value cannot be calculated. However, some studies showed that principal component extraction can still be performed using PCA without KMO calculation (Larsen and Baker, 2003;Cincinelli et al, 2007;Luo et al, 2008;Qin et al, 2012;Ngo et al, 2017). Therefore, in this research, although, the small sample size made it ineligible to perform Bartlett's test and KMO value calculation, the PCA still showed suitable principal components.…”
Section: Multivariate Data Analysismentioning
confidence: 97%
“…When performing PCA with the sample size smaller than the number of variables, (n < 17 in the case of PCDD/F), the KMO value cannot be calculated. However, some studies showed that principal component extraction can still be performed using PCA without KMO calculation (Larsen and Baker, 2003;Cincinelli et al, 2007;Luo et al, 2008;Qin et al, 2012;Ngo et al, 2017). Therefore, in this research, although, the small sample size made it ineligible to perform Bartlett's test and KMO value calculation, the PCA still showed suitable principal components.…”
Section: Multivariate Data Analysismentioning
confidence: 97%
“…By now, most of current studies on atmospheric PAHs focuses on a specific city or limited areas during short time period, such as in early autumn of 2008 , summer and autumn of 2008 (Wang et al, 2011) and in 2012 and 2013 (Lin et al, 2015a) in Beijing, in 2007 and in Hebei (Qin et al, 2012), and in summer of 2009 in Shanxi (Liu et al, 2014). As a result, direct comparison between studies cannot be made, and it is very hard to obtain PAH spatial variation in a large region.…”
Section: Introductionmentioning
confidence: 94%
“…The Atmospheric Chemistry and Climate Model Intercomparison Project (ACCMIP) was a multi-model initiative conducted to investigate the atmospheric abundance of key climate forcing agents, including tropospheric ozone, and their change over time (e.g. Stevenson et al, 2013;Lamarque et al, 2013). For our purposes, we use the ACCMIP climate model data as an example of a typical multi-model ensemble on which to perform the clustering.…”
Section: The Principles Of Cluster-based Ensemble Subsamplingmentioning
confidence: 99%
“…The k-means clustering algorithm, for example, is a relatively simple and popular technique used in several atmospheric science problems (e.g. Mace et al, 2011;Qin et al, 2012;Austin et al, 2013;Arroyo et al, 2017). Specifically related to climate science, clustering has also been used for automated classification of various remote-sensing data (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation